Investigation of Antioxidant and Hepatoprotective Activity of Standardized Curcuma xanthorrhiza Rhizome in Carbon Tetrachloride-Induced Hepatic Damaged Rats - Sutha Devaraj; Sabariah Ismail; Surash Ramanathan; Mun Fei Yam (The Scientific World Journal)
Curcuma xanthorrhiza (CX) has been used for centuries in traditional system of medicine to treat several diseases such as hepatitis, liver complaints, and diabetes. It has been consumed as food supplement and “jamu” as a remedy for hepatitis. Hence, CX was further explored for its potential as a functional food for liver related diseases. As such, initiative was taken to evaluate the antioxidant and hepatoprotective potential of CX rhizome. Antioxidant activity of the standardized CX fractions was determined using in vitro assays. Hepatoprotective assay was conducted against carbon tetrachloride- (CCl4-) induced hepatic damage in rats at doses of 125, 250, and 500 mg/kg of hexane fraction. Highest antioxidant activity was found in hexane fraction. In the case of hepatoprotective activity, CX hexane fraction showed significant improvement in terms of a biochemical liver function, antioxidative liver enzymes, and lipid peroxidation activity. Good recovery was observed in the treated hepatic tissues histologically. Hence, the results concluded that CX hexane fraction possessed prominent hepatoprotective activities which might be due to its in vitro antioxidant activity. These findings also support the use of CX as a functional food for hepatitis remedy in traditional medicinal system.